Application of combined endoscopic treatment of patients with bronchial stenosis after lung transplantation using thulium laser, balloon dilation, cryoablation, and airway stenting - M. T. Bekov; I. V. Pashkov; K. S. Smirnov; Ya. S. Yakunin; E. F. Shigaev; A. Z. Guluev; T. S. Kryukova; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2025)
Bronchial stenosis (BS) is a persistent, breathing-independent narrowing of the bronchial lumen, primarily brought on by scar and/or granulation tissue. BS occurring after lung transplantation tend to be recurrent, resulting in a higher frequency of hospitalizations compared to the group of patients without this complication. Minimally invasive endoscopic repair of the bronchial lumen is a generally recognized treatment for BS. This article demonstrates the experience of using a combined technique for restoring the lumen and preventing recurrent stenosis using thulium laser, balloon dilation, cryoablation, and stenting (hereinafter referred to as the combined technique).